Synthesis, Characterization and Biological Activity of Mn(II), Co(II), Ni(II), Cu(II), Zn(II), Pd(II), Cd(II), Pt(II), Hg(II) and Pb(II) Complexes of 2-Methyl-6-(3- phenylthioureido)benzoic Acid - H. Abdullah, Bayazeed; K. Kadir, Faraidoon (Asian Journal of Chemistry, 2010)
In this work, the synthesis, characterization and biological activities of Mn(II), Co(II), Ni(II), Cu(II), Pd(II), Pt(II), Hg(II) and Pb(II) complexes with 2-methyl-6-(3-phenylthioureido)benzoic acid (BH) are reported. The synthesized ligand (BH) and its metal complexes were characterized by elemental analysis, infrared and electronic spectral data, magnetic susceptibility and molar conductance. The biological activities of the synthesized complexes were tested against Staphylococcus aures, Escherichia coli and Pseudomonas aeruginosa using a well diffusion method. Dunnett method was used to compare the biological activities of the complexes with the control.